2022
DOI: 10.1128/spectrum.00910-22
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Pseudomonas putida To Produce Rhamnolipid Biosurfactants for Promoting Phenanthrene Biodegradation by a Two-Species Microbial Consortium

Abstract: Polycyclic aromatic hydrocarbons (PAHs), which are recalcitrant, carcinogenic, and tend to bioaccumulate, are widespread and persistent environmental pollutants. Based on these characteristics, the U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These aromatic compounds are not only difficult to degrade, but their hydrophobicity decreases their bioavailability. Previous studies have shown that rhamnolipids can enhance the solubilization and degradation of PAHs (37,50,51). We hypothesized that RLMEs would likely exhibit increased ability to solubilize PAHs compared to typical rhamnolipids due to their methyl ester functionality.…”
Section: Ecological Implications For Biosurfactant Production Within ...mentioning
confidence: 97%
See 1 more Smart Citation
“…These aromatic compounds are not only difficult to degrade, but their hydrophobicity decreases their bioavailability. Previous studies have shown that rhamnolipids can enhance the solubilization and degradation of PAHs (37,50,51). We hypothesized that RLMEs would likely exhibit increased ability to solubilize PAHs compared to typical rhamnolipids due to their methyl ester functionality.…”
Section: Ecological Implications For Biosurfactant Production Within ...mentioning
confidence: 97%
“…Rhamnolipid 1, first discovered from Pseudomonas aeruginosa (35), is known to exhibit antimicrobial properties and promote bacterial swarming motility (12)(13)(14)(15)(16)(17). Rhamnolipids have also been identified as potential mediators for uptake of hydrophobic substrates by P. aeruginosa and consortia (22,(36)(37)(38). As a result of carboxyl methylation, the typically anionic lipid region of rhamnolipids is neutralized in RLMEs, rendering this region even more lipophilic.…”
Section: Biosynthesis Of Rlmes Involves An Integral Membrane Methyltr...mentioning
confidence: 99%
“…Due to PAHs with low bioavailability, a surfactant-enhanced bioremediation method was developed, and the interface tension of oil–water was effectively reduced, and ultimately improved the restoration potential of artificial MMS for the contaminated site (Martinez-Toledo et al, 2022 ). During biodegradation by a two-species microbial consortium, a biosurfactant-secreting bacteria ( Pseudomonas aeruginosa ) was introduced into artificial MMS, and the biodegradation rates of PHE were significantly increased from 61.15% to 73.86% (Qin et al, 2022 ). The strong ability of cell proliferation and PAH degradation was shown by single bacteria (Llasera et al, 2021 ), but the above strain usually lacks a comprehensive metabolic pathway and enzyme system for hydrocarbons.…”
Section: Artificial Mms Construction Strategymentioning
confidence: 99%
“… Pseudomonas fluorescens AH-40 achieved 97 % degradation of 150 mg·L −1 phenanthrene within 15 days, which was faster than previously reported pure cultures [14]. Pseudomonas putida produces rhamnolipid biosurfactants, thereby promoting phenanthrene biodegradation [15]. Notably, most strains could only degrade low molecular weight PAHs (such as fluoranthene and phenanthrene) at low rates [16].…”
Section: Introductionmentioning
confidence: 97%